Religious institutes and Catholic culture in 19th- and 20th-century Europe - Altermatt, Urs; Maeyer, Jan de; Metzger, Franziska (KADOC studies on religion, culture, and society ;, 2014)
This volume examines the cultural contribution of religious institutes, men and women religious, and their role in the constitution of Catholic communities of communication in different European countries (England, Germany, Liechtenstein, the Low Countries, the Nordic Countries, Switzerland). The articles focus on social and cultural history by comparing both discourses and cultural and social practices, as well as examining international networks and cultural transference. How did religious institutes function as cultural elites in the production and mediation of knowledge, ideologies, cultural codes, and practices? What kind of discursive and operational strategies did they use to help construct and propagate social Catholicism, ultramontanism, and confessionalism, and to establish and promote the Catholic communication system? What were the central mechanisms in the production of knowledge and how were they incorporated within identity politics?0The volume also takes a broad perspective on the role of religious institutes in the production and propagation of religious, cultural, and social practices, and in the socialisation of the Catholic population. The focus is on cultural practices, on the transmission and transformation of attitudes, and on the rites and customs in everyday religious and social practices.